Ancient art and its commerce in early twentieth-century Europe : the John Marshall Archive : a collection of essays written by the participants of the John Marshall Archive Project - Petruccioli, Guido, (Archaeopress Publishing, 2022)
John Marshall (1862-1928) was an antiquities expert hired by the Metropolitan Museum of New York. An attentive observer of the antiquities trade, Marshall's archive, photographs and annotations on more than 1000 objects, shines light on the secretive world of art dealing and how objects arrived at the largest museums of Europe and North America.